PROYEKSI KEBIJAKAN BERBASIS KOMUNITAS BAGI PENDUDUK PESISIR DALAM MEWUJUDKAN KEHIDUPAN BERKELANJUTAN DAN PARIWISATA - Djafar, Franky; Akibu, Rifka (STISIPOL Mujahidin Buol, 2024)
Coastal communities have a strategic role in sustainable development, but face various challenges such as high population density, environmental degradation, and economic constraints. In Bajo Village, Tilamuta District, Boalemo Regency, Gorontalo Province, with an area of ​​only 0.25 km² and a population density of 7,036 people/km², this condition has a significant impact on environmental quality, infrastructure, and the ecotourism-based tourism sector. Socio-economic problems, such as slum settlements, limited basic facilities, and damage to marine ecosystems, have worsened the situation. This study aims to project community-based policies that can improve the quality of life of coastal residents while supporting the development of sustainable tourism. Using a qualitative approach, this study was conducted through in-depth interviews, participatory observation, and document analysis to explore the social, economic, and environmental dynamics of coastal communities in Bajo Village, Tilamuta District, Boalemo Regency, Gorontalo Province. The results of the study indicate that community-based policies, such as local economic empowerment, collective environmental management, and community capacity development in the tourism sector, can strengthen the balance between economic needs and environmental conservation. Active community participation in policy planning and implementation is a key factor for success. This study recommends a collaborative approach between government, local communities, and other stakeholders to create relevant, accountable, and sustainable policies.